2004
DOI: 10.7589/0090-3558-40.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Reproduce Vacuolar Myelinopathy in Domestic Swine and Chickens

Abstract: Avian vacuolar myelinopathy (AVM) was first recognized as a cause of bald eagle (Haliaeetus leucocephalus) mortality in 1994 in Arkansas (USA) and has since caused over 90 bald eagle and numerous American coot (Fulica americana) mortalities in five southeastern states. The cause of AVM remains undetermined but is suspected to be a biotoxin. Naturally occurring AVM has been limited to wild waterbirds, raptors, and one species of shorebird, and has been reproduced experimentally in red-tailed hawks (Buteo jamaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Species that specialize on dietary items that contain high levels of AVM toxin are most at risk (e.g., coots [hydrilla], and eagles [coots]; Birrenkott et al 2004;Lewis-Weis et al 2004). The density of A. hydrillicola colonies observed on Toho hydrilla is comparable to those in AVM reservoirs in South Carolina and Georgia (Wilde et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Species that specialize on dietary items that contain high levels of AVM toxin are most at risk (e.g., coots [hydrilla], and eagles [coots]; Birrenkott et al 2004;Lewis-Weis et al 2004). The density of A. hydrillicola colonies observed on Toho hydrilla is comparable to those in AVM reservoirs in South Carolina and Georgia (Wilde et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have confirmed that AVM toxin can be transferred up the food chain from herbivorous waterbirds to predatory raptors Birrenkott et al 2004;Lewis-Weis et al 2004). We predicted that Snail Kites would be susceptible to the toxin that causes AVM similar to Bald Eagles, Red-tailed Hawks (Buteo jamaicensis), and Great Horned Owls (Bubo virginianus) that developed AVM lesions after consuming prey from an AVM site (Lewis-Weis et al 2004).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations